An empirical evaluation of monetary and fiscal policy effects in Bangladesh. - Karim, Md. Shahnawaz (Metro Manila, Philippines Asian Development Bank, 2019)
Macroeconomic policy management is crucial for attaining sustainable economic growth with a stable a rate of inflation. In this working paper, monetary and fiscal policies in Bangladesh and their effectiveness in achieving sustainable growth and price stability are examined. It concludes that Bangladesh should focus on a combination of expansionary monetary policies and restrictive fiscal policies as the most beneficial approach.
Keywords: Fiscal policy -- Bangladesh; Industrial policy -- Bangladesh; Electronic books